Heterosis Manifestation in Rice (Oryza sativa L.) Hybrids under Water Limited Rainfed Condition - Jain, Abhinav; Payasi, Devendra; Reddy, K. R. Kamalnath; Shenoy, V. (International Journal of Bio-resource and Stress Management, 2023)
The three-line hybrid system involving cytoplasmic male sterile A- line, maintainer B-line and restorer R-line is a common approach for hybrid development in rice. The hybrids developed through this technique has been successful in increasing the rice production under favourable irrigated condition but hybrids under water-limited rainfed condition has not been much evaluated. Hybrids developed for non-irrigated rainfed lowland environment can help in sustaining the rice production under decreasing water and land resources. The emphasis therefore should be given for developing improved hybrids specifically suited for unfovourable water limited rainfed conditions. Keeping this in view, F1 crosses were generated using line x tester mating design to evaluate rice hybrids under rainfed stress. Assessment of heterosis in 64 F1 cross combination under water-limited rainfed condition revealed scope of exploiting hybrid vigour and developing heterotic hybrids for non-irrigated rainfed lowland environment. Significant standard heterosis over commercial hybrid checks (KRH 2 and PA 6444) observed in many cross combinations for various traits viz., filled grain per panicle, spikelet fertility percent, grain yield per plant, biomass per plant and harvest index highlight the importance of these traits in selecting parents based on above traits and developing hybrids with drought tolerance and high yield for water limited rainfed lowland ecology